PENGARUH INFORMASI ASIMETRIS DAN BIAYA TRANSAKSI TERHADAP CORPORATE GOVERNANCE DAN KINERJA ORGANISASI PUBLIK (STUDI KASUS PERUSAHAAN DAERAH AIR MINUM KABUPATEN MALANG) - EDDY PRIYANTO ; Prof.Dr.Maryunani, SE.,MS,Dr. M.Khusaini,SE.,MS.,MA,Dr. Ghozali Maskie,SE.,MS
Research on the relationship the agency has a lot to do but to date only limited to_x000D_ the intensity and perception in the business sector. This study aims to demonstrate_x000D_ comprehensively about the effects of asymmetric information and transaction costs on_x000D_ corporate governance and the performance of public organizations. _x000D_ The study employs a positivist paradigm using a quantitative approach, i.e testing_x000D_ the hypothesized influences between various variables. Object of study in Local Water_x000D_ Company in Malang regency, while the unit of analysis is the consumer/customer as the_x000D_ principal drinking water, Malang Regency Government as the owner (principal and agent)_x000D_ and PDAM Malang as manager as agent. _x000D_ The complexity of the relationship between the variables supported the concept of_x000D_ agency theory , transaction costs and make corporate governance Structural Equation_x000D_ Modeling as an appropriate tool to prove the hypothesis. _x000D_ The research proves that not all proposed hypothesis is accepted. Four of the six_x000D_ proposed hypotheses proved acceptable : (1) The direct effect of asymmetric information on_x000D_ the transaction costs in PDAM Malang, (2) direct effect of transaction costs on corporate_x000D_ governance PDAM Malang (3) The direct effect of transaction costs on the performance of_x000D_ public organizations through corporate governance, and (4) the effect of corporate_x000D_ governance on the performance of public organizations PDAM Malang. While the_x000D_ hypothesis that the influence of information asymmetries on corporate governance PDAM_x000D_ Malang proved to have no direct influence, as well as the effect of information asymmetry on_x000D_ the performance of public organizations PDAM Malang through proven corporate_x000D_ governance has no direct effect. _x000D_ _x000D_ _x000D_ _x000D_ Keywords : corporate governance, information asymmetry, transaction costs